Диффузия квазичастиц растворов ³Не- ⁴Не и классических частиц - Адаменко, И.И.; Немченко, К.Э. (Физика низких температур, 1995)
В рамках единого подхода вычислены все коэффициенты диффузии сверхтекучих растворов ³Не- ⁴Не и диффузионная матрица трехкомпонентного газа классических частиц. Показано, что диффузионный поток газа тепловых возбуждений определяет неаддитивную часть коэффициента теплопроводности раствора. По лученное выражение для коэффициента спиновой диффузии существенно отличается от эмпирической формулы, содержащей коэффициент массовой диффузии. Результаты расчетов сопоставляются с экспери ментальными данными. В межах единого підходу обчислено усі коефіцієнти дифузії надплинних розчинів ³Не- ⁴Не і дифузійна матриця трьохкомпонентного газу класичних частинок. Показано, що дифузійний поток газу теплових збуд жень визначає неадитивну частину коефіцієнта теплопровідності розчину. Одержаний вираз для коефіцієнта спінової дифузії істотно відрізняється від емпіричної формули, яка містить коефіцієнт масової дифузії. Ре зультати обчислень порівнюються з експериментальними даними. All diffusion coefficients of superfluid ³Не- ⁴Не mixtures and the diffusion matrix of a tree-component gas of classical particles were calculated using the com mon approach. The comparison of all the results ob tained made it possible to explain their physical sense. The diffusion flow of the gas of thermal excitations was shown to determine the nonadditive part of the thermal conductivity coefficient in the mixtures. The expression obtained for the coefficient of spin diffusion essentially differs from the earlier empirical formula that includes the coefficient of mass diffusion. The calculation results were compared with experimental data.